Changes in Tree Growth, Biomass and Vegetation Over a 13-Year Period in the Swedish Sub-Arctic - Henrik Hedenås; Håkan Olsson; Christer Jonasson; Johan Bergstedt; Ulrika Dahlberg; Terry V. Callaghan (AMBIO, 2011)
This study was conducted in the Swedish sub-Arctic, near Abisko, in order to assess the direction and scale of possible vegetation changes in the alpine—birch forest ecotone. We have re-surveyed shrub, tree and vegetation data at 549 plots grouped into 61 clusters. The plots were originally surveyed in 1997 and re-surveyed in 2010. Our study is unique for the area as we have quantitatively estimated a 19% increase in tree biomass mainly within the existing birch forest. We also found significant increases in the cover of two vegetation types—“birch forest-heath with mosses” and “meadow with low herbs”, while the cover of snowbed vegetation decreased significantly. The vegetation changes might be caused by climate, herbivory and past human impact but irrespective of the causes, the observed transition of the vegetation will have substantial effects on the mountain ecosystems.